Kurosawa to Kasdan: Storytelling influences. (1st June 2019) - Davies, Brett
Lawrence Kasdan is one of the most commercially successful screenwriters of the past forty years. In addition to writing Raiders of the Lost Ark (1981) and four episodes of the Star Wars saga, Kasdan has gained critical acclaim as the writer-director of seminal 1980s 'baby-boomer' films, such as The Big Chill (1983) and The Accidental Tourist (1988). Known for 'genre-hopping', it is perhaps Kasdan's very versatility that has led to a marked lack of academic discourse on his work, as his eclectic canon – including westerns, neo-noir, sci-fi horror, comedy and romantic thriller – makes it problematic for scholars to establish prevalent patterns in his output. This article argues that one influence has remained constant throughout Kasdan's career: the work of Akira Kurosawa. Examining three screenwriting elements – dialogue, protagonists, themes – the article will demonstrate how Kurosawa's storytelling style has repeatedly informed Kasdan's work, from his earliest screenplays (Kasdan said that 'there's a lot of Kurosawa in Raiders') to his most recent, as The Force Awakens (2015) and Solo: A Star Wars Story (2018) showed stylistic connections with Kurosawa's films, beyond those already established by George Lucas's original Star Wars (1977).